2009
DOI: 10.1007/s00216-009-3164-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of ß-amyloid oligomer-aggregates by ion mobility mass spectrometry and electron spin resonance spectroscopy

Abstract: Formation and accumulation of fibrillar plaques and aggregates of beta-amyloid peptide (Abeta) in brain have been recognized as characteristics of Alzheimer's disease (AD). Oligomeric aggregates of Ass are considered critical intermediates leading to progressive neurodegeneration; however, molecular details of the oligomerization and aggregation pathway and the structures of Abeta-oligomers are hitherto unclear. Using an in vitro fibril formation procedure of Abeta(1-40), beta-amyloid aggregates were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Since Aβ aggregation is a process that involves changes in protein conformation, native-PAGE is often a suitable technique to detect various sizes of Aβ species. A study by Iurascu et al used both SDS-PAGE and Tris-tricine PAGE to analyze the species formed by a solution of Aβ 1-40 solubilized in fibril growth buffer at pH 7.5 for 5 days at 37 °C [48]. They found that SDS-PAGE was able to detect Aβ 1-40 monomeric species, Aβ 1-40 oligomeric species of 20 kDa, and high molecular weight aggregates >98 kDa.…”
Section: Electrophoretic Techniques For the Quantification Of Aβ Omentioning
confidence: 99%
See 1 more Smart Citation
“…Since Aβ aggregation is a process that involves changes in protein conformation, native-PAGE is often a suitable technique to detect various sizes of Aβ species. A study by Iurascu et al used both SDS-PAGE and Tris-tricine PAGE to analyze the species formed by a solution of Aβ 1-40 solubilized in fibril growth buffer at pH 7.5 for 5 days at 37 °C [48]. They found that SDS-PAGE was able to detect Aβ 1-40 monomeric species, Aβ 1-40 oligomeric species of 20 kDa, and high molecular weight aggregates >98 kDa.…”
Section: Electrophoretic Techniques For the Quantification Of Aβ Omentioning
confidence: 99%
“…Iurascu et al . utilized SDS-PAGE in combination with MALDI-MS to analyze a solution of Aβ 1-40 solubilized in fibril growth buffer at pH 7.5 for 5 days at 37 °C [48]. MALDI-MS indicated that the soluble fraction contained two different ion mobilities, indicative of oligomerization.…”
Section: Spectroscopic Techniques For the Quantification Of Aβ Olimentioning
confidence: 99%
“…[65] These methods include recognition by specific anti-bodies, [66] mass spectrometry, [45] fluorescence resonance energy transfer (FRET), [58] and electrophoresis on native gel. [67] Furthermore, the morphology of the formed aggregates can be evaluated by means of microscopy (TEM or AFM). [49,68] Each of these techniques offers advantages but also suffers from drawbacks in terms of technique-related artifacts.…”
Section: Aggregationmentioning
confidence: 99%
“…Various techniques have been utilized to detect soluble and low-molecular weight oligomeric species formed by amyloid proteins such as atomic force microscopy (AFM) [12,14], light scattering [12,14], hydrogen-deuterium exchange mass spectrometry [15,16], matrix assisted laser desorption ionization mass spectrometry (MALDI-MS) [17,18], electrospray ionization mass spectrometry (ESI-MS) [19], ion mobility mass spectrometry (IM-MS) [2023], and oligomer specific antibodies [2426]. A major analytical challenge is developing a technique which is capable of identification, quantification, and characterization of a wide range of amyloid species.…”
Section: Introductionmentioning
confidence: 99%